PENAMBAHAN EKSTRAK JAHE (Zingiber officinale var Amarum) DAN EKSTRAK KUNYIT PUTIH (Curcuma zedoaria) PADA PEMBUATAN TELUR ASIN DENGAN VARIASI LAMA PEMERAMAN - Wibowo, Diky Gusnanto; Widanti, Yannie Asrie; Mustofa, Akhmad (Fakultas Pertanian, Universitas Sam Ratulangi, 2017)
Salted eggs is eggs preserved by marinated. The use of ginger extract in the salting solution can increase lipase enzyme activity that can decrease the fat content. The addition of white turmeric in foodstuffs can maintain its freshness and nutritional value, increase its palatability and to prolong the shelf-life. This study used a completely randomized design (CRD) consisting of 2 factors. The first factor was the ratio of ginger extract and turmeric extract (100 mL : 50 mL, 75 mL : 75 mL , and 50 mL : 100 mL) while the second factor was the duration of curing time (7, 14, and 20 days). The purpose of this study was to produce salted egg that have favored by consumers. The optimum result of this research was salted egg with 100 mL ginger extract, 50 mL turmeric extract, and 14 days ofÂ curing. Chemical characteristics of egg yolk: water (34.18%), fat (26.13%), peroxide number (6.03%), free fatty acid (FFA) (0.16%), and pH (6,1).The sensory characteristics of egg yolk: color (3.84), texture (3.84), ginger flavor (3.84), turmeric flavor (3.16), and overall preferences of panelists (4.68).Chemical characteristics of egg white: water (82.39%), fat (0.076%), peroxide number (0.791%), free fatty acid (FFA) (0.16%), and pH (8.45 %).The sensory characteristic of egg white: color (3.84), texture (3.84), ginger flavor (3), turmeric flavor (3.16), and overall favor of panelist (3.84).Keywords: ginger, long curing, salted egg, turmeric.